Penerapan Pendekatan Andragogi Dalam Meningkatkan Life Skill Masyarakat Melalui Pelatihan Daur Ulang Sampah Kantong Plastik - Syifa Mukharomah; Ansori Ansori; Novi Widiastuti (Comm-Edu (Community Education Journal), 2023)
Plastic waste is one of the wastes that is difficult to decompose naturally and requires a long time to decompose completey. Its single-use use results in a significant level of plastic bag consumption, resulting in the accumulation of plastic bag waste which can cause environmental pollution. The purpuse of this study was to describe the application of the andragogy approach in improving people’s life skill through training on recycling plastic bag waste. The research theory used are training theory, andragogy theory, and community education. The research theory used is descriptive with qualitative methods. Data collection techniques through interviews, observation, and documention. The main reason for using this instrument is to find out the appllication of the andragogy approach in improving people’s life skill through training on recyling plastic bag waste and obtaining research data as analytical material to support the prepation of reports. The results of this study illustrate the application of an andragogy approach through training on recycling plastic bag waste that can improve people’s life skill. The conclusion of this study is that this andragogy approach can increase people’s knowledge and skill in recycling plastic bag waste into various handicraft creations and can raise public awareness to reduce environmental pollition caused by the accumulation of plastic waste.